Ex post regulation of NGA networks: A roadmap for calculating the cost of an efficient operator – The case of Greece - Vangelis Logothetis; Nikos Ioannou; Markos Tselekounis; Dimitris Katsianis; Aris Chipouras; Dimitris Varoutas (International Telecommunications Society (ITS), 2019)
This paper provides a useful guide for telecom regulators on how to calculate the cost of an efficient operator investing in Next Generation Access (NGA) networks under regulatory uncertainty. When the regulator cannot make ex ante credible commitments, operators undertake their optimal investment decisions anticipating an ex post cost-oriented access regulation policy. Α roadmap for estimating the cost of an efficient operator deploying an NGA network under regulatory uncertainty is provided for the purposes of setting copper and NGA wholesale prices where cost orientation is imposed as a remedy. Following a detailed analysis, the most impactful parameters are identified and presented so as to trigger a fruitful discussion among academics, economists and policy makers.
Keywords: 330